Women workers in the household clothing industry and their contribution to household income in Sukun Malang Regency - Sari Yuniarti; Sugeng Haryanto (University of Merdeka Malang, 2005)
This study describes and analyzes women workers related to their income and contribution to family income in the household clothing industry. This is based on the reason that in the clothing industry the average working hours are longer than in other home industries. Women workers, especially those with families, when women work in the public sector are required to be able to divide their time between work and family. Women workers in the clothing sector work in an effort to increase family income, in order to cover the costs of daily needs. Most of the female workers are married, with the majority aged 21 to 40 years and with an average secondary education. The motivation of women workers in the clothing industry is mostly to increase family income. The additional income obtained from a working wife is certainly an important factor that is expected to reduce the burden on the family when the perceived price level is getting higher. The working time of women workers in the clothing industry is approximately 7 hours per day. The wage system is carried out every week every day. The income of female workers is relatively high, with the majority ranging from Rp. 71,000-80,000 per week. The income of married women workers shows that their income has a significant contribution to the increase in family income.